Ooplast-mediated developmental rescue of bovine oocytes exposed to ethidium bromide - Chiaratti, Marcos Roberto; Ferreira, Christina Ramires [UNESP]; Perecin, Felipe [UNESP]; Meo, Simone Cristina [UNESP]; Sangalli, Juliano Rodrigues; Mesquita, Ligia Garcia; de Carvalho Balieiro, Julio Cesar; Smith, Lawrence Charles; Garcia, Joaquim Mansano [UNESP]; Meirelles, Flavio Vieira (Elsevier B.V., 2011)
Ooplasm transfer has been used successfully to treat infertility in women with ooplasmic insufficiency and has culminated in the birth of healthy babies. To investigate whether mitochondrial dysfunction is a factor in ooplasmic insufficiency, bovine oocytes were exposed to ethidium bromide, an inhibitor of mitochondrial DNA replication and transcription, during in-vitro maturation (IVM). Exposure of immature oocytes to ethidium bromide for 24 h during IVM hampered meiotic resumption and the migration of cortical granules. However, a briefer treatment with ethidium bromide during the last 4 h of IVM led to partial arrest of preimplantation development without affecting oocyte maturation. Ooplasm transfer was then performed to rescue the oocytes with impaired development. In spite of this developmental hindrance, transfer of normal ooplasm into ethidium bromide-treated oocytes resulted in a complete rescue of embryonic development and the birth of heteroplasmic calves. Although this study unable to determine whether developmental rescue occurred exclusively through introduction of unaffected mitochondria into ethidium bromide-damaged oocytes, e. g. ethidium bromide may also affect other ooplasm components, these results clearly demonstrate that ooplasm transfer can completely rescue developmentally compromised oocytes, supporting the potential use of ooplasm transfer in therapeutic applications. (C) 2010, Reproductive Healthcare Ltd. Published by Elsevier Ltd. All rights reserved.
Keywords: Embryo; ethidium bromide; Mitochondrial DNA; Oocyte; ooplasm; transfer